Separation of Scaptotrigona postica Workers into Defined Task Groups by the Chemical Profile on Their Epicuticle Wax Layer - Poiani, Silvana B. [UNESP]; Morgan, E. David; Drijfhout, Falko P.; Cruz-Landim, Carminda da [UNESP] (Springer, 2014)
During evolution, the cuticle surface of insects acquired functions in communication, such as inter- and intra-specific recognition, identification of gender, physiological state, and fertility. In eusocial bees, the information in the cuticular surface is important not only to discriminate nestmates from non-nestmates but also to identify an individual's class, life phase or task. A comparative study of the cuticular surface chemical profile of workers of Scaptotrigona postica in different phases of life, i.e., newly emerged workers (NE), brood comb area workers (CA), and forager workers (FO) was undertaken by gas chromatography linked to mass spectrometry. Multivariate statistical analysis was performed to verify how workers are grouped according to their chemical profile and to determine which compounds are responsible for separating them into groups. The cuticle surface of workers contains mainly hydrocarbons and a small amount of oxygenated compounds. Multivariate statistical analysis showed qualitative and quantitative variation in relation to the life phases/tasks performed, and all groups were distinct. The most abundant compound found in NE and CA was n-heptacosane, while in FO, it was (Z)-9-heptacosene. The compounds that differentiate NE from other groups are n-tricosane and n-hexacosane. A (Z)-X-octacosene and n-nonacosane are the chemicals that distinguish CA from NE and FO, while 11- and 13-methylpentacosane, (Z)-X-hexacosene, and (Z)-9-heptacosene characterize FO as distinct from NE and CA. The probable function of alkenes is nestmate recognition, mainly in FO. The results show that the cuticle surfaces of workers are characteristic of the phase of life/task performed by workers, allowing intra-colonial recognition.
Keywords: Cuticular hydrocarbons; GC/MS analysis; Nestmate recognition; Social insect; Stingless bee; Hymenoptera; Apidae